2013
DOI: 10.19026/rjaset.5.4827
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Information and the Role of Accounting in Emerging Markets Evidences from TSE

Abstract: This study examines the value relevance (information content) of cash flow and accounting figures in situations where the information is asymmetrical and Compare the relative information content of them to clarify the role of accounting figures in investment decision making and mitigating the agency problems (specifically resulting from the existence of information asymmetry in the emerging markets). Based on testing a sample of 76 firms from Tehran Stock Exchange (TSE) during 2005 to 2011, the results support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…It also differed with the results of the study of (Szalavetz, 2015), where it showed that the autonomy of the manager in decision-making determines the exchange rate and being forced to some extent to meet the cost, whether actual or standard cost, which reflects negatively on the performance of this unit. Finally, the results of the current study showed that asymmetry of information has no impact on the performance of the sub-units and agreed with the results of the study of (Moradi et al, 2013) which showed that the problem of information asymmetry arises when one party monopolize information on the expense of other parties within the organization which lead to the preference of personal interest rather than the general interest of the organization. It also agreed with the results of the (Sacchi and Salotti, 2014), which showed that asymmetry of information, emerges with decentralization, so that most users of accounting information are unable to obtain the information they need.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It also differed with the results of the study of (Szalavetz, 2015), where it showed that the autonomy of the manager in decision-making determines the exchange rate and being forced to some extent to meet the cost, whether actual or standard cost, which reflects negatively on the performance of this unit. Finally, the results of the current study showed that asymmetry of information has no impact on the performance of the sub-units and agreed with the results of the study of (Moradi et al, 2013) which showed that the problem of information asymmetry arises when one party monopolize information on the expense of other parties within the organization which lead to the preference of personal interest rather than the general interest of the organization. It also agreed with the results of the (Sacchi and Salotti, 2014), which showed that asymmetry of information, emerges with decentralization, so that most users of accounting information are unable to obtain the information they need.…”
Section: Discussionsupporting
confidence: 89%
“…Frankline and Mayers (2016) noted that transfer price is considered as revenue for sales units and costs for purchasing units, so these prices affect their respective profits, since profit is one of the most important pillars for evaluating performance. Moradi et al (2013) indicated that the problem of information asymmetry arises because of the uniqueness of a party with information that is not available to the rest of the relevant parties within the organization, which leads to the preference of personal interest rather than general interest of the organization. (Sacchi and Salotti, 2014;Michalski et al, 2016) showed that asymmetry of information emerges with decentralization, causing the majority of users of accounting information to be unable to obtain the information they need.…”
Section: Information Asymmetry and Subsidiaries Performancementioning
confidence: 99%